The effects of sampling regime on the analysis of movements of overwintering female caribou in east-central Alaska - Joly, Kyle (Rangifer, 2005)
Global Positioning System (GPS) technology enables research of animal movements at finer levels of spatial and temporal resolution than previous methodologies allowed. A feature of GPS collar technology is the capability to program the dates of (sample period) and time between successive relocations (sample interval). I investigated the effects of sampling regime, the combination of sample period and interval, on analyzing movements of female caribou (Rangifer tarandus granti) in the Fortymile Caribou Herd as a case study. Based on hourly relocations throughout the winter, caribou moved 260 meters per hour or 6.2 kilometers per day. Sample period influenced estimates of movement rates, as I detected both diurnal and seasonal variability. Caribou movement rates during daylight and twilight hours were significantly greater than during the nighttime. Movement rates were greater during twilight hours than during daylight, but only slightly. Mid-winter and late winter movement rates were virtually the same, however, both were significantly less than during early winter. As sample interval increased, estimates of movement rates decreased substantially. Estimates based on 2-hour sample intervals were 14% less than those based on one-hour sample intervals, with estimates declining to 65% of the one-hour sample interval estimates at 167-hour (weekly) intervals. Estimates of home range were also affected by using different sampling intervals, however, kernel and MCP estimates responded antithetically to increasing sample interval. Researchers need to be aware that decisions about sampling regime can affect the estimates of ecological parameters that are based on relocations, such as movement rate, habitat selection, and home range.